Detection of infectious laryngotracheitis virus in trigeminal ganglia by avidin-biotin complex method in chickens: Short communication - Yilmaz, F; Timurkaan, N; Bulut, H (Akademiai Kiado Zrt, 2004)
Detection of infectious laryngotracheitis virus (ILTV) by avidin-biotin complex (ABC) method was studied in trigeminal ganglia (TRG) during the acute and post-acute or latent period in chickens inoculated with an A96 strain of the antigen. TRG tissue samples were collected from uninoculated (10 chickens) and inoculated (30 chickens) animals at various intervals post inoculation (PI), and stained by the ABC method. The results indicated that no ILTV antigen was detected in the TRG between PI days 3 and 11. However, the antigen was detected in most of the chickens between PI days 13 and 41. It is concluded that the ABC method can be used successfully for the detection of ILTV antigens in TRG during post-acute or latent period.
Keywords: chicken; infectious laryngotracheitis virus; trigeminal ganglia; avidin-biotin complex